The Role Of Credit Rating Agencies In Malaysia - Sahamid, Badariah (Journal of Malaysian and Comparative Law, 2002)
Since 1990 to date, corporations which wanted to issue corporate bonds were required to obtain a rating from one of the two rating agencies in Malaysia, Rating Agency Malaysia Bhd (RAM) or Malaysian Rating Corporation (MARC).